Evaluasi Peforma Benih Indigofera zollingeriana dari Tanaman Berbeda Umur - Kathleya Rosadi; Luki Abdullah; Nur Rochmah Kumalasari (Buletin Ilmu Makanan Ternak, 2018)
Seed production could be affected by plant age due to different physiological activity. These research aimed to evaluate the effect of different age on Indigofera zollingeriana seeds production and characteristics. The study was conducted on plants at 1, 4, and 8 years old. The variables measured were pods production, pods characteristics, seed weight, and seed characteristics. Data were analyzed by Analysis of Variance Matrix Unbalance by software R 3.3.2 and Correlation Analyses.  Results showed that plant age increased  (p<0.01) pods length and diameter; and seed diameter and thickness. Plant age had positive corellation to increased dry weight of pods, seed weight, percentage of seed weight per pods, average weight of 1000 seeds. It concluded that plant age could increasing pods length and diameter; and seed characteristics.  Therefore, I. zollingeriana plant could be seed sources until 8 years old